Hubungan Tingkat Keparahan dan Tingkat Kontrol dengan Kualitas Hidup Pasien Asma Bronkial di Poli Paru RSUD dr. H. Moch. Ansari Saleh Banjarmasin - Risma Dwi Rahimah; Olviani, Yurida; Julianto Julianto; Solikin Solikin (PPNI UNIMMAN, 2025)
Bronchial asthma is a chronic respiratory disease that significantly impacts the quality of life of sufferers. The severity and level of asthma control are important factors in determining a patient's condition. Data from the Pulmonary Clinic of Dr. H. Moch. Ansari Saleh Regional General Hospital (RSUD) show an increase in the number of asthma patients every year, necessitating further analysis of the factors that influence the quality of life of sufferers. This study aims to analyze the relationship between severity and control levels and the quality of life of bronchial asthma patients. This study used an observational analytical design with a cross-sectional approach. The study sample consisted of 47 respondents selected using a purposive sampling method according to the inclusion criteria. The instruments used included a severity questionnaire based on the Global Initiative for Asthma (GINA) guidelines, the Asthma Control Test (ACT), and the Mini Asthma Quality of Life Questionnaire (Mini-AQLQ). Data analysis was performed using the Kendall's Tau-b test with a significance level of 0.05. The results showed that the majority of respondents were female (53.2%) and aged 31–45 years (36.2%). The highest asthma severity was mild persistent (29.8%), while the most dominant level of control was fully controlled (38.3%). The quality of life of the respondents was mostly in the moderate category (38.3%). Statistical tests showed a significant relationship between severity and quality of life (p = 0.003) and between control and quality of life (p = 0.001). It can be concluded that the higher the level of asthma severity, the lower the patient's quality of life tends to be, while better asthma control is associated with a better quality of life. These results emphasize the importance of early detection, optimal asthma control, and regular monitoring by healthcare professionals to improve patients' quality of life.